IMPACT DE L’UTILISATION DU LOGICIEL SYDONIA A LA DIRECTION GENERALE DES DOUANES ET ACCISES DANS LA MAXIMISATION DES RECETTES PUBLIQUES Cas de la Direction de la Province Orientale de 2010 à 2015 - LILEMBE, Godelieve OMONDO (IJRDO - Journal of Business Management, 2022)
Speaking about the impact of the use of the software SYDONIA to the Directorate-General of the Customs and Excises in maximization of the public receipts: Case of the Management of the Eastern Province of 2010 to 2015, we left the assumption according to which the use of this software to the Directorate-General of the Customs and Accises would improve the level of the receipts poured with the Treasury. There was some discussion about comparing the receipts poured with the account of the Treasury with the use of SYDONIA to those versed before its advent. The had aim is to check if the computerization of the customs system in RDC with the advent of software SYNONIA++ contributed effectively to the improvement of the receipts carried out compared to those carried out at the time of the manual system.The results of this research show that the advent of SYDONIA contributes effectively to the improvement of the receipts carried out by this financial control that the manual system (before SYDONIA).